Maturity Level Framework ITIL V3 dalam Mengukur Kepuasan Mahasiswa Terhadap Web Student Universitas Amikom Purwokerto - Sri Wahyuningsih; Oktafia Heng Huice; Ito Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
In this era of globalization, technology increasingly influences education. Students of Amikom University Purwokerto use Web Student to access academic information such as schedules and grades. Although educational technology is developing, challenges in meeting student needs still exist. Evaluation is needed to assess the effectiveness of Web Student, especially in user satisfaction. This study uses ITIL Version 3 in the service operation domain, with a Likert scale-based questionnaire to 60 respondents to measure the maturity level. The results of the maturity level include: event management 2.90, incident management 2.45, problem management 2.13, request fulfillment 2.24, and access management 3.18. Overall, the average index of all questionnaire results variables obtained was 2.58, which is on a scale of 3 out of 5 maturity levels, namely defined.